2014
DOI: 10.1016/j.elspec.2014.08.003
|View full text |Cite
|
Sign up to set email alerts
|

Thermal evolution of the band edges of 6H-SiC: X-ray methods compared to the optical band gap

Abstract: The band gap of semiconductors like silicon and silicon carbide (SiC) is the key for their device properties. In this research, the band gap of 6H-SiC and its temperature dependence were analyzed with silicon 2p x-ray absorption spectroscopy (XAS), x-ray emission spectroscopy (XES) and resonant inelastic x-ray scattering (RIXS) allowing for a separate analysis of the conduction-band minimum (CBM) and valence-band maximum (VBM) components of the band gap. The temperature-dependent asymmetric band gap shrinking … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 25 publications
1
9
0
Order By: Relevance
“…These small energetic changes in combination with the shift of the Si L 3 absorption edge point to a decrease in the band gap energy with temperature. A detailed discussion is beyond the scope of this paper and will be conducted elsewhere [46]. The changes in the features of the RIXS spectra with temperature will be dealt with in the following subsections.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These small energetic changes in combination with the shift of the Si L 3 absorption edge point to a decrease in the band gap energy with temperature. A detailed discussion is beyond the scope of this paper and will be conducted elsewhere [46]. The changes in the features of the RIXS spectra with temperature will be dealt with in the following subsections.…”
Section: Resultsmentioning
confidence: 99%
“…We would like to point out that the feature appearing in the middle panel around 99 eV increasing for the 300-900°C is an indirect result of the shift of the valence band maximum with temperature shortly mentioned above. In a separate paper we analyze the band gap, the valence band maximum and conduction band minimum of 6H-SiC as a function of temperature [46]. The RIXS spectra indicated with C in the left panel of figure 1 do not seem to show this valence band maximum shift, but after zooming in one may recognize a small but nonnegligible shift in the valence band maximum as a function of temperature [46].…”
Section: Am Transfermentioning
confidence: 97%
“…For more complex materials strain engineering provides an attractive alternative method for tailoring materials' properties beyond what is possible through doping or chemical substitution. 10,14 As combination of X-ray absorption and emission spectroscopy, Resonant Inelastic X-ray Scattering (RIXS), is specific for determining electronic structure properties such as the band gap, 15 covalent interactions, 16 potential energy surfaces 17 and excited states 18 with element-and oxidation-state specificity. In this report it will be shown that RIXS is also sensitive to changes in electronic structure due to induced strain.…”
Section: Introductionmentioning
confidence: 99%
“…They offer many potential applications in many kinds of optoelectronic devices, such as solar cells [2][3][4], temperature and gas sensors [5,6], protective coatings [1] full-color electroluminescent display [7], and light emitting diodes [5,[8][9]. By varying the carbon concentrations in a-SiC films, the optical gap (Eg) can be continuously tuned in a wide range, which makes it useful for devices design and performances [10], and thus the electrical and optical properties can be manipulated to better suit the application in photovoltaic heterojunction devices [8,11].…”
Section: Introductionmentioning
confidence: 99%